Peran Pentahelix dalam Pengembangan Usahatani Sayur Desa Sukorambi, Kecamatan Sukorambi, Kabupaten Jember - Luthfiyah, Lenny; Subekti, Sri; Mustapit, Mustapit (Fakultas Pertanian Universitas Jember, 2024)
Sukorambi Village, Sukorambi District, Jember Regency has potential for vegetable production. However, farmers experience problems related to seeds, scarcity of fertilizer, pests and diseases, and fluctuations in vegetable prices. The existing potential for vegetable farming needs to be developed. This research aims to look at the role of pentahelix, academics, business, community, government and media in the development of vegetable farming in Sukorambi Village. This research uses qualitative methods which are presented descriptively. Data collection methods were carried out using in-depth interviews, non-participatory observation, and documentation. Informants were determined using purposive sampling. Data validation uses triangulation. Data were analyzed using the Miles and Huberman interactive model. The research results show that academics play a role in research and community service related to vegetable cultivation and farmer health. However, some of the programs initiated did not run sustainably. The business sector plays a limited role in introducing pesticide products. Business parties who contribute to the income are restaurant entrepreneurs who purchase vegetables. The role of the community is manifested in the formation of farmer group institutions, HIPPA and Gapoktan as a forum for networking, discussion and conveying aspirations. The Regency Government and Village Government play a role in providing agricultural equipment, agricultural infrastructure improvements and grant funds. Meanwhile, the media's role is very minimal. The production of published information on the vegetable potential of Sukorambi Village is very limited. Collaboration between helixes needs to be improved by strengthening the role of the Jember Regency government and Village Government as regulators and controllers. The government has made an MoU with academics, business and the media regarding an effective vegetable farming development program. Mass media and social media owned by the government and the community produce information related to the vegetable potential of Sukorambi Village. The government carries out supervision so that the role of pentahelix can be carried out consistently, sustainably and have positive implications for the development of vegetable farming in Sukorambi Village.